Peningkatan Hasil Belajar Materi Bangun Datar melalui Model Pembelajaran Index Card Match pada Peserta Didik Kelas II SDN 1 Kebumen Tahun Ajaran 2017/2018 - Tuti Winarni (Universitas PGRI Semarang, 2019)
This research is motivated by the low learning outcomes of students in grade II flat material SDN 1 Kebumen. The purpose of this study was to improve mathematics learning outcomes of flat figure material through the Index Card Match (ICM) learning model for grade II students of SDN 1 Kebumen, amounting to 22 students with 13 male students and 9 female students. The research was conducted on April 9, 2018 until May 11, 2018. This study used the Classroom Action Research (CAR) pathway which was conducted in two cycles. Each cycle consists of 2 meetings. Each meeting consists of 4 steps, namely planning, implementation, observation and reflection. Data collection is done by observation and test techniques. Observation sheets were analyzed descriptively, while the learning outcomes tests were analyzed with Minimum completeness criteria (KKM). The results showed an increase in completeness from 23% in pre-cycle, to 45% in cycle I, and 100% in cycle II. The average student learning outcomes increased from 55.90 in the pre-cycle, to 68.54 in the first cycle, and 90.09 in the second cycle. Thus it can be concluded that the application of the Index Card Match learning model can improve student learning outcomes.